Assessing Participatory Practices in a Cultural Preservation Workshop of the Sriwijaya Museum - Adiwan F Aritenang; Zahara Sitta Iskandar; Pingkan Safitri; Riela Provi Drianda; Laila Zohrah (Journal of Regional and City Planning, 2021)
Among the great maritime trading empires of history, the Sriwijaya empire ranks among the most splendid and rich ones. Still, few people know about this empire and recognize it as an important part of the history of Indonesia. This study examined participatory practice in historic preservation by investigating stakeholders’ perspectives on the potential application of digital technology in the Sriwijaya Museum in Palembang. We introduced photogrammetry and color analysis technologies to identify some possible improvements to be implemented in the museum in the future. We invited some community members interested in Palembang’s history and in using digital technology in museums to participate in a two-day participatory workshop. Pre-workshop and post-workshop questionnaires were distributed to identify the participants’ expectations for and responses to the workshop. Moreover, we also interviewed several participants. The study revealed that all participants agreed that both technologies have great potential to provide narrations in the museum and support thematic activities such as arts, culinary, and music performances. This paper highlights the importance of the local community’s commitment and the government’s political will to realize a roadmap for the city’s cultural heritage preservation and digitization movement.   Abstrak. Di antara kerajaan perdagangan maritim besar dalam sejarah, Sriwijaya termasuk yang paling megah dan terkaya. Namun, hanya sedikit orang yang mengetahui dan mengakui Kerajaan Sriwijaya sebagai bagian penting dari sejarah Indonesia karena penggalian lebih banyak artefak dan sisa-sisa rumit. Tulisan ini bertujuan untuk mengkaji praktik partisipatif dalam pelestarian sejarah dengan mengkaji perspektif pemangku kepentingan tentang potensi penerapan teknologi di Museum Sriwijaya. Kami memperkenalkan teknologi fotogrametri dan analisis warna untuk mengidentifikasi beberapa perbaikan yang mungkin diterapkan di masa depan. Kami mengundang beberapa anggota masyarakat yang tertarik menggunakan teknologi di museum untuk berpartisipasi dalam lokakarya dua hari tersebut. Kuesioner pra dan pasca dibagikan untuk mengidentifikasi tanggapan dan harapan peserta terhadap lokakarya. Selain itu, kami mewawancarai beberapa peserta. Studi tersebut mengungkapkan bahwa semua peserta sepakat bahwa kedua teknologi tersebut berpotensi diterapkan untuk memberikan narasi di museum dan mendukung kegiatan tematik, seperti seni, kuliner, dan pertunjukan musik. Kajian tersebut menyoroti pentingnya komitmen masyarakat lokal dan kemauan politik pemerintah untuk mewujudkan peta jalan gerakan pelestarian warisan budaya dan digitalisasi kota.   Kata kunci. partisipatif, workshop, pelestarian budaya, alat digital, Museum Sriwijaya.